Gene-Eden-VIR: A Potential Natural Treatment for Cervical Cancer - Hanan Polansky; Will Blesch (Journal of Cervical Cancer, 2016)
This paper explores the potential of Gene‑Eden‑VIR as an adjunctive approach for cervical cancer prevention or management. The discussion reviews proposed antiviral and immunomodulatory mechanisms, existing evidence, and safety considerations. The authors call for controlled trials to clarify efficacy and appropriate clinical use.
Keywords: Cervical Cancer